2013
DOI: 10.1038/srep02011
|View full text |Cite
|
Sign up to set email alerts
|

Metallic behaviour in SOI quantum wells with strong intervalley scattering

Abstract: The fundamental properties of valleys are recently attracting growing attention due to electrons in new and topical materials possessing this degree-of-freedom and recent proposals for valleytronics devices. In silicon MOSFETs, the interest has a longer history since the valley degree of freedom had been identified as a key parameter in the observation of the controversial “metallic behaviour” in two dimensions. However, while it has been recently demonstrated that lifting valley degeneracy can destroy the met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Interaction amplitudes γs , γ t , γ v and conductivity σ xx are taken at the length scale L T = σ xx /zT . It is instructive to compare result (86) with the result for the situation when one of the quantum wells is not filled by electrons. This corresponds to the limit d → ∞.…”
Section: Dephasing Timementioning
confidence: 99%
See 2 more Smart Citations
“…Interaction amplitudes γs , γ t , γ v and conductivity σ xx are taken at the length scale L T = σ xx /zT . It is instructive to compare result (86) with the result for the situation when one of the quantum wells is not filled by electrons. This corresponds to the limit d → ∞.…”
Section: Dephasing Timementioning
confidence: 99%
“…We mention that recently 2D two-valley electron system in SiO 2 /Si(100)/SiO 2 quantum well has been experimentally studied. 85,86 However, in Ref. 86 the inter valley scattering rate was estimated to be of the order of 7 K such that 2D electron system behaves as single valley one for transport at low temperatures (T 7 K).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental research into the physical consequences of valley polarizing a two-dimensional electron system in the steady state is led by studies of AlAs and Si-based structures. It has been demonstrated that valley polarization dramatically affects phenomena such as the fractional quantum Hall effect 11 12 13 14 and the metal insulator transition 15 16 17 18 , two effects in which electron–electron interactions are central. Pioneering experiments performed in AlAs indicate that valley polarization also has a strong impact on another effect where electron–electron interactions play crucial roles: spin polarization.…”
mentioning
confidence: 99%